Rassismus : Von der frühen Bundesrepublik bis zur Gegenwart - Vukadinović, Vojin Saša 1979- HerausgeberIn (De Gruyter, 2022)
Racism is once again an issue in Germany. Few studies have addressed the changing manifestations of racism in West Germany and in post-1990 Germany. The essays in this collection trace an arc of continuity from post-1945 völkisch ideology to the beginnings of right-wing terrorism, to the consequences of legislation concerning foreigners, and to issues of identity politics